PATH-25. LEPTOMENINGEAL, DURAL, AND EXTRACRANIAL METASTASIS OCCUR IN DIVERSE TYPES OF ADULT HIGH-GRADE GLIOMA. (14th November 2022) - Travers, Sarah; Kleinschmidt-DeMasters, B K; Ryan Ormond, D
Abstract: BACKGROUND: Leptomeningeal and extracranial metastases in adult high-grade gliomas are being increasingly recognized as critical issues. Our group has a longstanding interest in this issue, having published multiple examples in 2015 (PMID: 26308254) and 1996 (8617464). We now update our experience, illustrating that dissemination can occur in diverse types of high-grade gliomas, even those with purportedly more favorable prognoses. METHODS: Search of records, 2018-present, to identify patients with leptomeningeal, dural, and/or extracranial spread clinically recognized prior to patient demise. RESULTS: Leptomeningeal dissemination was identified in 6 patients: one astrocytoma (frontal lobe, IDH1 R132H+, metastatic to 3-levels spinal cord), a second astrocytoma (frontal lobe, IDH1 R132H+, metastatic to spinal cord with intracranial dissemination), one glioblastoma, small cell type ( PIK3CA, CDH1, TP53 mutations, temporal lobe metastatic to cervical cord), one high-grade glioma with piloid features (HGAP, metastatic at presentation; BRAF -mutant, classified by DNA methylation (NIH)) and one high-grade glioma with no match to DNA methylation class (metastatic at presentation, NIH). There were three additional patients: one patient with glioblastoma with FGFR : TACC3 fusion with short-interval dural and cervical lymph node metastases (in Press), one patient with glioblastoma with EGFR amplification and dural invasion and one patient with glioblastoma with massive dural spread and bony invasion at presentation. CONCLUSION: Although these new 9 individual cases provide no insights into the epidemiology of GBM leptomeningeal, dural and extracranial metastases, our single-institution series, using updated molecular classifications not always available in retrospective studies, shows that dissemination can occur in any, and all, types of adult high-grade gliomas. We put this cohort in perspective with our experience with dissemination in other low and high-grade tumor types: anaplastic myxopapillary ependymomas (30417460), H3 K27M-altered high-grade gliomas (29393845), pineal parenchymal tumors of intermediate differentiation (34418607), myxoid glioneuronal tumor, PDGFRA-mutant (34297434) and spinal cord gangliogliomas (25015869).